Bevacizumab biosimilar LY01008 compared with bevacizumab (Avastin) as first‐line treatment for Chinese patients with unresectable, metastatic, or recurrent non‐squamous non–small‐cell lung cancer: A multicenter, randomized, double‐blinded, phase III trial. Issue 9 (29th June 2021) - Shi, Yuankai; Lei, Kaijian; Jia, Yuming; Ni, Bingqiang; He, Zhiyong; Bi, Minghong; Wang, Xicheng; Shi, Jianhua; Zhou, Ming; Sun, Qian; Wang, Guolei; Chen, Dongji; et al.
Abstract: Background: Previous studies have demonstrated the preclinical pharmacological and toxicological consistency, and clinical pharmacokinetic equivalence of bevacizumab biosimilar LY01008 with reference bevacizumab (Avastin). This randomized controlled trial aimed to compare the efficacy and safety of LY01008 with Avastin in first‐line treatment of Chinese patients with advanced or recurrent non‐squamous non‐small cell lung cancer (NSCLC). Methods: Stage IIIB‐IV NSCLC patients with evaluable lesions, good physical status, and adequate organ functions from 67 centers across China were randomized in a ratio of 1:1 to receive LY01008 or Avastin 15 mg/kg intravenously in combination with paclitaxel/carboplatin (combined treatment) for 4‐6 cycles, followed by maintenance monotherapy with LY01008 until disease progression, intolerable toxicity, or death. The primary endpoint was objective response rate (ORR) in accordance with Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 confirmed by independent radiological review committees (IRRC). Secondary endpoints included disease control rate (DCR), duration of response (DoR), progression‐free survival (PFS), overall survival (OS), and safety. This study was registered in ClinicalTrials.gov (NCT03533127). Results: Between December 15 th, 2017, and May 15 th, 2019, a total of 649 patients were randomized to the LY01008 ( n = 324) or Avastin ( n = 325) group. As of September 25 th, 2019 for primary endpoint analysis, 589 patients received ORR evaluation, with a median number of combined treatment cycles of 5 (range 1‐6) and median duration of treatment of 3.0 (range 0.0‐5.1) months. ORR of response‐evaluable patients in the LY01008 and Avastin groups were 48.5% and 53.0%, respectively. The stratified ORR ratio was 0.91 (90% CI 0.80‐1.04, within the prespecified equivalence margin of 0.75‐1.33). Up to May 15 th, 2020, with a median follow‐up of 13.6 (range 0.8‐28.4) months, no notable differences in DCR, median DoR, median PFS, median OS, and 1‐year OS rate were observed between the LY01008 and Avastin groups. There were no clinically meaningful differences in safety and immunogenicity across treatment groups. Conclusions: LY01008 demonstrated similarity to Avastin in terms of efficacy and safety in Chinese patients with advanced or recurrent non‐squamous NSCLC. LY01008 combined with paclitaxel/carboplatin is expected to become a new treatment option for unresectable, metastatic, or recurrent non‐squamous NSCLC patients in the first‐line setting. Abstract : This study demonstrated similarity between LY01008 and reference bevacizumab (Avastin) in terms of efficacy, safety, and immunogenicity in combination with paclitaxel and carboplatin as first‐line treatment in Chinese patients with advanced non‐squamous NSCLC.